A Characterization of Multi-Wavelet Dual Frames in Sobolev Spaces - Jianping Zhang; Jiajia Li (Journal of Function Spaces)
For the past few years, wavelet and multi-wavelet frames have attracted interest from researchers. In this paper, we address some of these problems in the setting of the Sobolev space, and characterize of multi-wavelet dual frames in these spaces by using a pair of equations.